Complementarities between fiscal policy and monetary policy - literature review - Wei Dong; Geoffrey Dunbar; Christian Friedrich; Dmitry Matveev; Romanos Priftis; Lin Shao (Bank of Canada, 2021)
This paper reviews and summarizes the literature on the complementary relationship between fiscal policy and monetary policy. We focus on four types of fiscal policy: (1) automatic stabilizers, (2) state-contingent non-discretionary fiscal policy, (3) discretionary fiscal stimulus and (4) government credit policies. The literature shows that automatic fiscal stabilizers can play a role in stabilizing business cycle fluctuation. But because they can have multiple policy objectives, their optimal design remains an open question. An alternative policy framework features state-contingent non-discretionary fiscal expenditures with a pre-committed fiscal spending formula triggered by objective macroeconomic conditions. Such a policy offers the advantage of being timely and easy to communicate; but at the same time, it poses challenges for identifying appropriate triggers and program expenditures with high short-run multipliers. The literature also shows that discretionary fiscal expenditures can support aggregate demand, and some expenditures have short-run multipliers close to, or above, 1. While these expenditures can focus on specific policy priorities that are relevant at the time, their discretionary nature may slow the policy response. When interest rates are close to the effective lower bound (ELB), fiscal stimulus can be particularly effective for complementing the stabilizing efforts of monetary policy. Finally, studies show that government credit policies can mitigate economic downturns that are accompanied by severe financial market distress. However, the effects of scaling up this channel are uncertain.
Keywords: E52; E62; E58; E63; 330; Fiscal policy; Monetary policy